2019
DOI: 10.1515/jisys-2017-0143
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Approach to Decision Support System Design for Inventory Control and Management

Abstract: The ubiquitous nature of inventory and its reliance on a reliable decision support system (DSS) is crucial for ensuring continuous availability of goods. The DSS needs to be designed in a manner that enables it to highlight its present status. Further, the DSS should be able to provide indications about subtle and large-scale variations that are likely to occur in the supply chain within the context of the decision-making framework and inventory management. However, while dealing with the parameters of the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…On the contrary, if the various organizations within the supply chain restrict each other, there is friction or conflict, or the links are not smoothly connected, it will inevitably cause unnecessary waste of the internal organization of the entire supply chain, causing the entire supply chain to fall into a disordered state. Mahuya Deb et al [2] built a neuro-fuzzy system (NFS) for an inventory control decision support system to control production and supply. Wenfang Yu [3] and others proposed a more systematic and improved supply chain inventory optimization model based on the ant colony algorithm and the basic idea of a fuzzy model for the problem of high inventory in supply chain management.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, if the various organizations within the supply chain restrict each other, there is friction or conflict, or the links are not smoothly connected, it will inevitably cause unnecessary waste of the internal organization of the entire supply chain, causing the entire supply chain to fall into a disordered state. Mahuya Deb et al [2] built a neuro-fuzzy system (NFS) for an inventory control decision support system to control production and supply. Wenfang Yu [3] and others proposed a more systematic and improved supply chain inventory optimization model based on the ant colony algorithm and the basic idea of a fuzzy model for the problem of high inventory in supply chain management.…”
Section: Introductionmentioning
confidence: 99%
“…However, this condition is avoided when the flow of information circulating in the supply chain runs smoothly and which automatically forms a supply chain that is more likely to be a centralized planner [15]. Besides, previous studies have suggested factors that encourage sellerbuyer relationships for flexibility, as well as discounts in product quantity [16], [17], and payment options [18].…”
Section: Introductionmentioning
confidence: 99%